Analisis dampak pertumbuhan populasi terhadap peningkatan volume sampah di Gili Trawangan - Bagustiandi , Tatas (Institute for Advanced Social, Science, and Sustainable Future, 2024)
Background: Gili Trawangan, one of the famous tourist destinations on the island of Lombok, is facing the problem of increasing waste volume caused by population growth and rapid tourism activities. This research aims to analyze the impact of population growth on increasing waste volume on Gili Trawangan during the 2024-2033 period. Methods: The method used in this research is waste growth prediction analysis by referring to the results of population projections and standardization of the amount of waste generation. Findings: The data used includes the population of Gili Trawangan over the last 10 years, waste generation per individual, and waste density. Conclusion: The research results show that population growth on Gili Trawangan is increasing every year with an average growth rate of 1.09%. The weight of waste generated per person is 0.7 kg/person/day, while the volume of waste generated per person is 5.6 liters/person/day. The projected total daily waste weight on Gili Trawangan in 2033 is estimated to reach 1.24 tons/day, with an annual total waste weight of 452.60 tons. The total daily waste volume in 2033 is estimated to reach 9.92 m3/day. The conclusion of this research is that population growth and increased tourism activities are the main factors influencing the increase in the volume of waste generation on Gili Trawangan. Comprehensive and sustainable waste management efforts are needed, such as implementing the 3R principle (Reduce, Reuse, Recycle) to overcome waste problems in stages. The results of this research can be a reference for local governments and related stakeholders in planning and developing an effective and efficient waste management system in Gili Trawangan, in order to preserve the environment and support sustainable tourism in the area.